Depression and anxiety in primary caregivers at Instituto Nacional de Salud del Niño - Aranda-Paniora, Franklin (2017)
Objective: Depression and anxiety in primary caregivers of pediatric inpatients. Design: Clinical, cross-sectional, descriptive study. Location: Instituto Nacional de Salud del Niño, Lima, Peru. Participants: Primary caregivers of pediatric inpatients. Interventions: Goldberg test for depression, anxiety and comorbidity was applied to 240 primary caregivers of pediatric inpatients in 2014-2016. Results: 87.5% of primary caregivers presented some type of disorder: comorbidity 57%, anxiety 13.5%, and depression 17%; 12.5% did not present any disorder. Conclusions: The frequency of anxiety and depression in primary caregivers of pediatric patients is greater than in the general population.